Nutrient mixture inhibits in vitro and in vivo growth of human acute promyelocytic leukemia HL-60 cells - Roomi, M.W.; Roomi, N.W.; Bhanap, B.; Rath, M.; Niedzwiecki, A. (Experimental Oncology, 2011)
Aim: Untreated acute promyelocytic leukemia is the most malignant form of acute leukemias, with median survival of less than one month. We investigated in vitro and in vivo synergistic effects of a nutrient mixture (NM) containing ascorbic acid, lysine, proline, and green tea extract, on acute promyelocytic leukemia HL-60 cells. Methods: In vitro, the HL-60 cells were cultured and exposed to NM at doses 0–1000 μg/ml. Cell viability was assessed by Trypan blue dye exclusion test, matrix metalloproteinases (MMP) expression by gelatinase zymography, invasion through Matrigel and apoptosis by live green Poly Caspase Detection Kit. In vivo studies were carried out in athymic nude mice subcutaneously inoculated with HL-60 cells. Results: In vitro, NM exhibited a dose dependent reduction in cells viability. Zymography revealed matrix MMP-2 and phorbol 12-myristate 13-acetate induced MMP-9 expression. NM inhibited expression of both MMP in a dose dependent manner. Similar step-wise reduction in the Matrigel invasion by HL-60 cells was also observed by this combination with incremental doses. Gradually increasing doses of NM induced significant apoptosis in HL-60 cells. In vivo, NM inhibited tumor growth by 50%. Conclusion: The results indicate that NM significantly suppresses tumor growth, decreases cell viability, inhibits MMP expression, Matrigel invasion and induces apoptosis in HL-60 cells.